A universal method to fabricating porous carbon for Li-O2 battery. (April 2021) - Zhao, Tuo; Yao, Ying; Yuan, Yifei; Wang, Meiling; Wu, Feng; Amine, Khalil; Lu, Jun
Abstract: The main bottleneck in the application of biomass-based carbon material in energy field is the development of an economical, nanoscale controllable and universal fabrication method. Herein, we demonstrate that a biomass-derived carbon consisting of loose carbon nanosphere clusters could serve as an ideal cathode material for high performance Li-O2 batteries. The carbon nanomaterial can be prepared from both biomass derivatives and crude biomass by a low cost, facile and nanoscale controllable method. The open slit-shaped hierarchical pore structure endows the electrode sufficient active surface sites and mass transport channels that are not easily asphyxiated by the discharge products. The concentration of oxygenic groups and structure defects on the surface of obtained carbon materials is very low, which minimizes the side reactions associated with carbon decomposition. The unique pore structure and surface properties of the carbon electrode give rise to a superhigh specific capacity of 20, 300 mA h g −1 and an extremely long cycle life which a cyclic capacity retention of 100% is maintained for 543 cycles with current density of 0.2 mA cm −2 at controlled discharge-charge depths of 500 mA h g −1 . Graphical Abstract: ga1 Highlights: Universal, low-cost, facile and nano-texture controllable fabrication method. Carbon nanosphere clusters featuring an open slit-shaped pore structure. Open pores expose the reactive sites fully and prevent the mass transport channels from being blocked. Fast reaction kinetics, ultra-high specific capacity and long cycle life as cathode for Li-O2 batteries.